The new sorts and hybrids of vegetable crops for conditions of glass-cove red ground. - В. А. Кравченко; Н. І. Янчук (Plant Varieties Studying and Protection)
The short characteristica of new sorts and hybrids of vegetubles for greenhouses cultivation are presented. All sorts and hybrids in researches were included in State Regster of Plant Varieties Suitable for Dissemination in Ukrains in 2010.